Morphological characterization of vaginal epithelial cells of santa inês ewes subjected to estrus synchronization - Ribeiro, Camila Vasconcelos; Neves, Tábatta Arrivabene; Fagundes, Glaucia Brandão; do Nascimento, Dayana Maria; da Silva, Cleidson Manoel Gomes; Arrivabene, Mônica; Dias, Francisca Elda Ferreira; Cavalcante, Tânia Vasconcelos (Comunicata Scientiae, 2019)
Vaginal cytology analysis has been used to evaluate the different stages of estrous cycle of several species; it presents a direct correlation with the animal’s hormonal state and provides essential information about the female reproductive tract conditions. Two staining methods were tested to evaluate the vaginal epithelial cell morphology of nulliparous and multiparous ewes during the estrus period. An intravaginal device impregnated with medroxyprogesterone acetate was kept into 10 nulliparous and 10 multiparous ewes for 14 days for estrus synchronization. Then, the progesterone device was withdrawn, and 300 IU of eCG was administered intramuscularly. Vaginal smears were prepared for posterior staining with Panotico or Giemsa stains when estrus was detected. The cells were classified into nucleated superficial, anucleate superficial, intermediate, parabasal, and basal. The Panotico and Giemsa staining of the different cell types studied were satisfactory. A predominance of intermediate epithelial cells (p<0.05) was found after staining. No difference in percentages of the different types of vaginal epithelial cells between nulliparous and multiparous ewes were found. Therefore, both staining methods were efficient, and a predominance of intermediate cells is found in nulliparous and multiparous ewes during the estrus period.